Old firms and new products: Does experience increase survival? - Martina Lawless; Zuzanna Studnicka (University College Dublin, UCD School of Economics, 2018)
We examine the relationship between exporting experience and the duration of firm export product flows. We find that more experienced firms (in years of exporting) show a higher probability of failure associated with the introduction of new products. On the other hand, firms with broader export scope are more likely to have better survival times for newly launched products. Although apparently counter-intuitive, we show that this finding is consistent with models of multi-product firms in which firms begin exporting by launching the products closest to their core competency and gradually expand their range of products by exporting those that are further away from their core, resulting in lower survival probability for later products. Validating this interpretation, we show that the distance of the new products to the core competency of the firm plays an important role in determining the survival of new products.
Keywords: F10; 330; Duration of Trade; Firm Survival; Export Experience; Multi-product firms